The determinants of consumers' inflation expectations: Evidence from the US and Canada - Charles Bellemare; Rolande KpekouTossou; Kevin Moran (Bank of Canada, 2020)
We propose and estimate a dynamic and individual model of expectations formation that links individual consumers' inflation expectations to their own lagged forecasts as well as proxies for the rational expectation forecasts. The model builds on the existing rational inattention literature and extends it in several dimensions. We explicitly model the expectations updating rule which consumers use to incorporate new information in their experience and take seriously heterogeneity in inflation expectations extensively documented in the literature. We estimate the model using data from two important new surveys - the Federal Reserve Bank of New York's Survey of Consumer Expectations and the Bank of Canada's Canadian Survey of Consumer Expectations. We find that inflation expectations appear to correlate more strongly to measures of rational expectations forecasts in Canada than in the US, and conversely less to lagged expectations. More specifically, the median respondent assigns overall weights of roughly 75% to proxies for the rational expectation forecasts and 25% to lagged expectations in Canada, while these weights are around 50-50 for the US. We show that these differences in weights are not explained by differences in the characteristics of their stand-in consumers. Given this finding, one candidate explanation could be related to the explicit inflation target in Canada in comparison to the dual mandate in the US.
Keywords: C33; D83; D84; E31; 330; Central bank research; Econometric and statistical methods; Inflation and prices; Inflation targets